Online Access to the Encyclopaedia Slavica Sanctorum - Goynov, Maxim; Paneva-Marinova, Desislava; Dimitrova, Margaret (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2011)
Encyclopaedia Slavica Sanctorum project aims at building a repertoire of medieval and early modern Bulgarian texts for saints in combination with ethnological data and some visual sources. A basic project task is to produce an accessible on-line digital repository of this valuable cultural heritage treasure. The paper presents the Encyclopaedia Slavica Sanctorum environment, its architecture, functional specification, application modeling process and software implementation. The paper also discusses the specifics of the ―Encyclop a edia Slavica Sanctorum‖ project and its knowledge domain. The paper also presents the integration between the Encyclopaedia Slavica Sanctorum and the Bulgarian Iconographical Digital Library, a digital library keeping rare specimens, private collections of Orthodox icons, wallpaintings and other iconographical objects, selected from difficult-to-access storages, distant churches, chapels, and monasteries, objects in a risk environment or unstable conditions.